2020
DOI: 10.1016/j.ijheatmasstransfer.2020.119683
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer analysis in an uncoiled model of the cochlea during magnetic cochlear implant surgery

Abstract: Magnetic cochlear implant surgery requires removal of a magnet via a heating process after implant insertion, which may cause thermal trauma within the ear. Intra-cochlear heat transfer analysis is required to ensure that the magnet removal phase is thermally safe. The objective of this work is to determine the safe input power density to detach the magnet without causing thermal trauma in the ear, and to analyze the effectiveness of natural convection with respect to conduction for removing the excess heat. A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
(43 reference statements)
1
4
0
Order By: Relevance
“…This means that natural convection heat transfer (second term on the lefthand side of ( 8)) is negligible in comparison to conduction (right-hand side of ( 8)). This result is in agreement with our previous study performed on an uncoiled cochlea model [4], where it was shown that natural convection has a negligible impact on the thermal management of the scala tympani during magnetic cochlear implant surgery. As such, heat transfer by natural convection is neglected in the remainder of this paper.…”
Section: Experimental Design and Scale Analysissupporting
confidence: 93%
See 1 more Smart Citation
“…This means that natural convection heat transfer (second term on the lefthand side of ( 8)) is negligible in comparison to conduction (right-hand side of ( 8)). This result is in agreement with our previous study performed on an uncoiled cochlea model [4], where it was shown that natural convection has a negligible impact on the thermal management of the scala tympani during magnetic cochlear implant surgery. As such, heat transfer by natural convection is neglected in the remainder of this paper.…”
Section: Experimental Design and Scale Analysissupporting
confidence: 93%
“…The removal can be accomplished by melting the substance bonding the implant electrode array and the magnet via localized heating. Consequently, the magnet detachment process may cause localized hyperthermia within the scala tympani, which is one of the more serious impediments preventing the establishment of magnetic cochlear implant surgery [4], [5]. Localized hyperthermia in the ear, which is not unique to magnetic cochlear implant surgery, arises in a variety of applications such as infrared neural stimulation implants [6] - [10], stapedectomy [11], [12], caloric test [13], [14], and radio-frequency radiation devices such as cellular phones [15] - [17].…”
Section: Introductionmentioning
confidence: 99%
“…Radiation heat transfer is negligible because of the low temperatures involved (around the body core temperature of 37 • C) within the cochlea during the magnet detachment process [15]. The implant EA forces some of the perilymph out of the cochlea and, consequently, reduces the impact of natural convection to a negligible value with respect to conduction heat transfer [14,15]. Perfusion and metabolic heat generation are both negligible in com- b Calculated based on the information provided by MED-EL [28].…”
Section: Description Of the Physical And Mathematical Modelsmentioning
confidence: 99%
“…It was previously shown that an input power density of 1.8 MW m 3 for 114 s is required to melt 1 mm 3 of paraffin bonding the magnet to the EA (under the assumption that the boundaries of the paraffin are adiabatic and no heat is wasted) [14,15]. Here, the minimum safe input power density for 114 s of heating is determined to be 20 MW m 3 , which is more than 11 times larger than the required input power density to melt the paraffin.…”
Section: Impact Of Boundary Conditions and Heating Durationmentioning
confidence: 99%
See 1 more Smart Citation